Resurrection of the genus Subulo Smith, 1827 for the gray brocket deer, with designation of a neotype - Bernegossi, Agda Maria [UNESP]; Borges, Carolina Heloisa de Souza [UNESP]; Sandoval, Eluzai Dinai Pinto [UNESP]; Cartes, Jose Luis; Cernohorska, Halina; Kubickova, Svatava; Vozdova, Miluse; Caparroz, Renato; Gonzalez, Susana; Duarte, Jose Mauricio Barbanti [UNESP] (Oxford Univ Press Inc, 2022)
The gray brocket deer, Mazama gouazoubira, occurs in South America and presents an extensive degree of morphological and genetic variability. Previous phylogenetic research showed that the genus Mazama is polyphyletic and imposed the designation of a different genus-group name for M. gouazoubira. We aimed to review and clarify the taxonomy of M. gouazoubira through the proposal of updating the nomenclature for this taxon and by the characterization of specimens collected close to the original type locality (topotypes). The topotypes were characterized by morphological (general characterization and morphometry), cytogenetic (conventional staining, Ag-NOR, G- and C-banding, and fluorescence in situ hybridization), and phylogenetic (mitogenomes) approaches. We revealed chromosome homologies between cattle and M. gouazoubira using an entire set of cattle whole chromosome painting probes and propose an updated G-band idiogram for the species. The morphometric analysis did not discriminate the individuals of M. gouazoubira, including the topotypes, from other small brocket deer species. However, the phylogenetic analysis, based on a Bayesian inference tree of the mitogenomes, confirmed the polyphyly of the genus Mazama and supported the need to change the gray brocket deer genus-group name. Based on our revision, we validated the genus Subulo, and fixed a type species for the genus. In the absence of the holotype, we denominated a neotype described by the collection of a male topotype in Paraguay. The nomenclature rearrangement presented here is a starting point that will assist in the taxonomic resolution of Neotropical deer.
Keywords: Cytogenetics; Mazama; Mitogenome; Phylogeny; Taxonomy; Cervideos; Citogenetica; Filogenia; Mitogenoma; Taxonomia